Aberrant sensorimotor coupling and movement planning in complex regional pain syndrome. Issue 5 (17th May 2023) - Floegel, Mareike; Steinmetz, Sebastian; Dimova, Violeta; Kell, Christian A.; Birklein, Frank
Abstract : Patients with complex regional pain syndrome have altered movement planning: movement started earlier, brain activation contralateral to the complex regional pain syndrome limb was influenced by anxiety, and sensorimotor regions demonstrate higher coupling. Abstract: Complex regional pain syndrome (CRPS) is characterized by inflammation and a failure of multimodal signal integration in the central nervous system (CNS). Central nervous system reorganization might account for sensory deficits, pain, and motor symptoms in CRPS, but it is not clear how motor control is affected by CNS mechanisms. The present study characterized the motor performance and related cortical activity of 16 CRPS patients and 16 control participants during the planning of visually guided unimanual grips, in patients with either the unaffected left or the affected right hand, and investigated resting-state sensorimotor coupling in MRI. Patients started isometric movements further in advance of the "go" cue and earlier than control participants. Even when accounting for this different timing, results showed side-independent overactivation in planning-related sensorimotor regions in CRPS during manual grips and increased functional coupling between those regions at rest. Fear of movement or individual pain scores contributed only marginally to the observed effects. The study suggests that changes in planning-related sensorimotor CNS regions may explain difficulties with force exertion and motor control in CRPS. Perspective : Functional changes in motor planning-related brain regions might indicate that feedback-enhanced functional motor training may be effective for CRPS rehabilitation.